2018
DOI: 10.1016/j.envint.2018.08.042
|View full text |Cite
|
Sign up to set email alerts
|

HIV induced nitric oxide and lipid peroxidation, influences neonatal birthweight in a South African population

Abstract: HIV has been implicated in adverse birth outcomes, due to increased oxidative stress and inflammation. In addition, HIV has been reported to increase nitric oxide levels. Therefore the combined exposures to HIV and traffic-related air pollution, within South Durban, South Africa (SA), may lead to adverse birth outcomes. However, the exact mechanism is still unknown; this study aimed to identify a potential mechanism. First, the influence of HIV on oxidative and nitrosative stress markers in pregnant women was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…HIV infection in adults is associated with an accentuated risk of alcohol and substance use in many settings [34]. Air pollution and environmental toxins (such as mycotoxins) are also potential risk factors for poor child growth [50, 51]. There is some evidence that HIV-infected individuals may have higher mycotoxin levels despite the same exposure when compared to HIV-uninfected controls.…”
Section: Pathogenesis—universal Pathways Versus Hiv-specific Pathways?mentioning
confidence: 99%
See 1 more Smart Citation
“…HIV infection in adults is associated with an accentuated risk of alcohol and substance use in many settings [34]. Air pollution and environmental toxins (such as mycotoxins) are also potential risk factors for poor child growth [50, 51]. There is some evidence that HIV-infected individuals may have higher mycotoxin levels despite the same exposure when compared to HIV-uninfected controls.…”
Section: Pathogenesis—universal Pathways Versus Hiv-specific Pathways?mentioning
confidence: 99%
“…Mycotoxin exposure may plausibly exacerbate several pathways underlying HIV pathogenesis (including enteropathy and micronutrient deficiencies), thereby affecting early growth [54]. Additionally, the interacting effects of air pollutants and HIV have been associated with adverse birth outcomes, potentially through increasing nitric oxide levels [51].…”
Section: Pathogenesis—universal Pathways Versus Hiv-specific Pathways?mentioning
confidence: 99%
“…Interestingly, miR-144 appears to mediate influenza-induced lung injury as ablating miR-144 in vivo attenuates influenza replication and lung injury in mice. 41 However, to date, studies connecting HIV-1 and miR-144 have been few and far between, including one recent clinical investigation 42 and our own recent paper on HIV-1-induced epithelial dysfunction. 16 In summary, we determined that HIV-1 infection of human macrophages, or the chronic expression of HIV-1 viral proteins within the alveolar space in a transgenic animal model, induces miR-144.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with healthy pregnant women [ 31 ], MDA concentrations were elevated in the first gestational trimester. In addition, Anderson et al [ 36 ] demonstrated that high levels of MDA influenced the low birth weight of newborns from HIV-positive mothers compared to those without the infection.…”
Section: Discussionmentioning
confidence: 99%